MAKASSAR HAJJ HOSPITAL : HARMONISATION OF SERVICES WITH CLINICAL PRACTICE GUIDELINES AND ISLAMIC PRINCIPLES - Syukur, Muhammad; Suhaeb, Firdaus W; Ibrahim, Irviani Anwar (Homes Journal = Hospital Management Studies Journal, 2024)
Background: In the accreditation standard of hospitals in Indonesia, the preparation and application of clinical guidelines is indeed required in the form of a Clinical Practice Guide (PPK), especially for patient management with high risk. The accreditation standard also requests that PPK also be the basis for conducting the quality and safety of patients provided by each clinicali. In addition, it is needed by the Islamic Health Services which apply Sharia principle. The problem that is usually buried is how to implement Islamic values in management and health services in hospitals. Objective: This study aims to determine the standard of services that are in accordance with the clinical practice guide (PPK) and the management of Islamic services at the Makassar General Hospital in Haji Regional Hospital. Method: The research method used a type of qualitative research with an approach. Result: The results obtained from the interview conducted, the Hajj Hospital has provided services that are in accordance with clinical practice guidelines and Islamic services standards at the Hajj Hospital have been well gone. Conclusion: Haji Hospital has provided services in accordance with clinical practice guidelines, clinical pathways and service standards. The form of these services is generally in accordance with Standard Operating Procedures (SOP).